2016
DOI: 10.1152/ajplung.00178.2015
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal BAY 41-2272 reduces pulmonary hypertension in the rabbit model of congenital diaphragmatic hernia

Abstract: Infants with congenital diaphragmatic hernia (CDH) fail to adapt at birth because of persistent pulmonary hypertension (PH), a condition characterized by excessive muscularization and abnormal vasoreactivity of pulmonary vessels. Activation of soluble guanylate cyclase by BAY 41-2272 prevents pulmonary vascular remodeling in neonatal rats with hypoxia-induced PH. By analogy, we hypothesized that prenatal administration of BAY 41-2272 would improve features of PH in the rabbit CDH model. Rabbit fetuses with sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…In fact, in the rabbit model, only two studies have been published and have reported a decrease in eNOS in CDH lungs compared with controls, but no disruption in VEGF or ET pathways. 139,140 In the sheep model of CDH, there are a few more studies, indicating similar findings to those observed in the nitrofen model: an altered interaction between dysfunctional EC and PASMCs via increased expression of ET-1 and decreased eNOS. [141][142][143] However, contrarily to what has been reported in the nitrofen model, ECs of CDH lamb lungs had a higher expression of VEGF and its receptors compared with those of controls.…”
Section: Discussionsupporting
confidence: 56%
“…In fact, in the rabbit model, only two studies have been published and have reported a decrease in eNOS in CDH lungs compared with controls, but no disruption in VEGF or ET pathways. 139,140 In the sheep model of CDH, there are a few more studies, indicating similar findings to those observed in the nitrofen model: an altered interaction between dysfunctional EC and PASMCs via increased expression of ET-1 and decreased eNOS. [141][142][143] However, contrarily to what has been reported in the nitrofen model, ECs of CDH lamb lungs had a higher expression of VEGF and its receptors compared with those of controls.…”
Section: Discussionsupporting
confidence: 56%
“…Rabbits with surgical diaphragmatic hernias received a single dose of BAY 41–2272 via tracheal instillation on E28 ( 58 ), and were retrieved at term. Results showed reduced right ventricular pressure and ameliorated vascular remodeling with decreased medial thickening in small arteries and increased capillary formation.…”
Section: Antenatal Cdh-ph Pharmacotherapiesmentioning
confidence: 99%
“…Rojas-Moscoso et al and Vuckovic et al reported that different soluble guanylyl cyclase activators (BAY 60-2770 and BAY 41-2272) induced relaxant responses of the pulmonary artery in vitro, as well as in vivo when administered intratracheally. 146,147 Russo et al performed an antenatal maternal treatment with sildenafil during the last 6 days of rabbit pregnancy (from 24 to 30 days of gestation) and demonstrated rescue of vascular branching and architecture, decreased pulmonary vascular resistances, and improved airway morphometry and respiratory mechanics. 148…”
Section: Interventions Tested Using the Rabbit Modelmentioning
confidence: 99%